Pengaruh Model TPS dan Kebiasaan Membaca terhadap Keterampilan Menulis Deskriptif Siswa SMP di Jakarta Pusat - Siti Rodiyah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This study aimed to determine the effect of using the Think-Pair-Share (TPS) model and students' reading habits on descriptive writing skills in English subjects at the junior high school level. The research method used is experimentation with data processing using SPSS. The researcher gave the TPS learning model treatment and then differentiated reading interest habits into two groups, namely groups with high and low reading interest. After that, students are asked to do a written test to make a simple descriptive paragraph. The sample used is private junior high school students in Central Jakarta. The total number of students involved in this study was 30 students. This study showed the effect of TPS treatment and students' reading habits. However, if you look at the data, the differences between the two are insignificant for the ability to write descriptively in English subjects at the junior high school level.